1977
DOI: 10.1159/000148901
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Human Cytomegalovirus and Herpesvirus Hominis IgM Antibody by the Immunoperoxidase Technique

Abstract: Immunoglobulin M (IgM) to human cytomegalovirus (CMV) and herpesvirus hominis (HVH, types 1 and 2) has been searched for in a group of patients with congenital and recent CMV and HVH infections and also in a group of patients with remote CMV and recurrent HVH infections, using the immunoperoxidase antibody technique (IPA) as compared to a technique using sucrose density gradient differential centrifugation. Both techniques detected the same positive samples. High IgM antibody titers (1:32–1:512) were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It may be assumed that most of these patients had a reactivation of a previous CMV infection or a reinfection with CMV. Other investigators (1,6,16) have also observed that a proportion of patients with evidence or reactivation or reinfection with CMV did produce IgM antibody.…”
Section: Discussionmentioning
confidence: 89%
“…It may be assumed that most of these patients had a reactivation of a previous CMV infection or a reinfection with CMV. Other investigators (1,6,16) have also observed that a proportion of patients with evidence or reactivation or reinfection with CMV did produce IgM antibody.…”
Section: Discussionmentioning
confidence: 89%
“…In the group of five reactivated CMV infections, CMV elimination was always associated with detection of EA-Ab at different titers. In the three groups of subjects (healthy people, leukemic children, and pregnant women) tested for presence of CMV EA-Ab, the prevalence of this antibody was 6 of 31 leukemic children, 4 of 28 pregnant women, and 3 of 17 healthy people.…”
Section: Resultsmentioning
confidence: 98%
“…In developing the test, the type of CMV antigen used for coating of polystyrene beads was of greatest importance. Antigens prepared from CMV-infected cell suspensions, the most commonly used antigen in CF tests and in previously reported RIA [Knez et al, 19761 and ELISA tests [Gerna et al, 1977[Gerna et al, , 1978Cappel et al, 1978;Ziegelmaier et al, 1978; P h a and Pejtsik, 19791 produced high background values, unsatisfactory specific binding, and titration curves with inverted slope in IgG assays. A possible explanation for this may be CMV-induced Fc-binding, which is supported by the facts that the control antigen gave markedly less cpm than cell-associated CMV antigen when used in titrations of negative reference sera in IgG assays and that the inverted slope was not seen with the control antigen.…”
Section: Dlscusslonmentioning
confidence: 99%
“…Detection of cytomegalovirus (CMV)-specific antibodies by enzyme-linked immunosorbent assay (ELISA) and solid-phase radioimmunoassay (RIA) has been described by several authors [Knez et al, 1976;Gerna et al, 1977Gerna et al, , 1978Cappel et al, 1978;Ziegelmaier [Sarov et al, 19801 of these studies, antigens prepared from infected cell suspensions were used. Among possible pitfalls in CMV serology are false-positives due t o CMV-induced IgG-(Fc) receptors [Furukawa et al, 1975;Betts et al, 1976;Keller et al, 1976;Rahman et al, 1976;Griffiths et al, 19781, anticell antibodies [The and Langenhuysen, 1972;Anderson and Andersen, 19781 and rheumatoid factors [Gispen et al, 1975;Knez et al, 1976;Meurman et al, 1977;Cremer et al, 1978;Krishna et al, 19801, The present report describes a radioimmunoassay in which extracellular CMV harvested by ultracentrifugation was adsorbed on polystyrene beads and antibodies that reacted with the virus antigen were assayed by iodinated anti-human IgG, IgM, and IgA.…”
Section: Introductionmentioning
confidence: 99%